Considerations in the Efficacy and Effectiveness of Virtual Reality Interventions for Stroke Rehabilitation: Moving the Field Forward. Issue 3 (1st March 2015) - Proffitt, Rachel; Lange, Belinda
Abstract : In the past 2 decades, researchers have demonstrated the potential for virtual reality (VR) technologies to provide engaging and motivating environments for stroke rehabilitation interventions. Much of the research has been focused on the exploratory phase, and jumps to intervention efficacy trials and scale-up evaluation have been made with limited understanding of the active ingredients in a VR intervention for stroke. The rapid pace of technology development is an additional challenge for this emerging field, providing a moving target for researchers developing and evaluating potential VR technologies. Recent advances in customized games and cutting-edge technology used for VR are beginning to allow for researchers to understand and control aspects of the intervention related to motivation, engagement, and motor control and learning. This article argues for researchers to take a progressive, step-wise approach through the stages of intervention development using evidence-based principles, take advantage of the data that can be obtained, and utilize measurement tools to design effective VR interventions for stroke rehabilitation that can be assessed through carefully designed efficacy and effectiveness trials. This article is motivated by the recent calls in the field of rehabilitation clinical trials research for carefully structured clinical trials that have progressed through the phases of research.